Association of ambient pollution with inhaler use among patients with COPD: a panel study. Issue 5 (13th March 2018) - Magzamen, Sheryl; Oron, Assaf P; Locke, Emily R; Fan, Vincent S
Abstract : Background: Studies have linked ambient air pollution to chronic obstructive pulmonary disease (COPD) healthcare encounters. However, the association between air quality and rescue medication use is unknown. Objectives: We assessed the role of air pollution exposure for increased short-acting beta-2-agonist (SABA) use in patients with COPD through use of remote monitoring technology. Methods: Participants received a portable electronic inhaler sensor to record the date, time and location for SABA use over a 3-month period. Ambient air pollution data and meteorological data were collected from a centrally located federal monitoring station. Mixed-effects Poisson regression was used to examine the association of daily inhaler use with pollutant levels. Four criteria pollutants (PM2.5, PM10, O3 and NO2 ), two particulate matter species (elemental carbon (EC) and organic carbon), estimated coarse fraction of PM10 (PM10–2.5 ) and four multipollutant air quality measures were each examined separately, adjusting for covariates that passed a false discovery rate (FDR) screening. Results: We enrolled 35 patients with COPD (94.3% male and mean age: 66.5±8.5) with a mean forced expiratory volume in 1 s (FEV1 ) % predicted of 44.9+17.2. Participants had a median of 92 observation days (range 52–109). Participants' average SABA inhaler use ranged from 0.4 to 13.1 puffs/day (median 2.8). Controlling for supplemental oxygen use, long-acting anticholinergic use, modified Medical Research Council Dyspnoea Scale and influenza season, an IQR increase in PM10 concentration (8.0 µg/m 3 ) was associated with a 6.6% increase in daily puffs (95% CI 3.5% to 9.9%; FDR <0.001). NO2 and EC concentration were also significantly associated with inhaler use (3.9% and 2.9% per IQR increase, respectively). Conclusions: Exposure to increased ambient air pollution were associated with a significant increase in SABA use for patients with COPD residing in a low-pollution area.